Quality of Coconut Oil using Fruit of Dwarf Coconut - Karouw, Steivie; Indrawanto, Chandra; Novarianto, Hengky (International Coconut Community, 2015)
The purpose of this research was to study processing of coconut oil which focused on evaluation of the quality of oil by using fruit of several Dwarf coconut as raw materials. The varieties used were Salak Green Dwarf (SGD), Raja Brown Dwarf (RBD) and Bali Yellow Dwarf (BYD). The oil was extracted through the wet process by heating technique. The coconut oil volume was measured and evaluated for its fatty acids profile, free fatty acid contents, moisture content, color, smell and taste. The by-products such as coconut residue and blondo were measured, too. The results showed that processing of oil from 200 Dwarf nuts produced 7.1-8.4 L. The highest volume of oil (8.4 L) was resulted from SGD. The oil was generally having high medium chain fatty acid around 58.50-62.32% including lauric acid at 46.82-48.46%. The oil made from fruits of SGD contained the highest lauric acid around 48.46%, followed by RBD and BYD reaching 48.06% and 46.82%, respectively. It had a good smell, and fatty acid and moisture content were in accord with Indonesian National Standard. The coconut oil processed using the fruit of the SGD and RBD has a clear white color, while the BYD having clear yellow in color, like corn oil.